E-readiness and technology use in teaching by library and information science lecturers in Nigeria (2016)
The current trend globally in higher education institutions is student-centred learning which can be facilitated through the use of technology’ for teaching and learning. This allows for learning to take place not only in the classroom but also outside the classroom. It also affords the students the opportunity to interact with different information resources and technology, their colleagues and the lecturers. This necessitates the deployment of technology by Library and Information Science lecturers. The use of technology requires the awareness of such technology, benefits and acquisition of Information and Communication Technology skills. However, literature has revealed that some lecturers are still reluctant to adopt technology for their teaching because it is time consuming and they do not have the requisite skills. This paper highlights the benefits, types, skills and institutional support required to facilitate the use of technology for teaching and learning by lecturers in library schools in Nigeria. It concludes that LIS lecturers need develop ICT skills and adopt technology for their teaching and learning. It recommends that the management of universities in Nigeria should provide the necessary institutional support for the use of technology by the lecturers in library schools.